International trade and inclusive economic growth : a case study of Peru and China - Bustinza, Harold Delfin Angulo (Emerald Publishing Limited, 2024)
Examining economic growth through the lens of poverty, social exclusion, and economic inequality, Harold Delfin Angulo Bustinza offers an econometric analysis of the effects of international trade between Peru and China, which has seen an average annual growth of 22% over the past two decades. China thus plays a key role in Peru's economic growth, whether in imports of primary goods, exports of capital and consumer goods, or direct investment. However, income and wealth inequality in Peru have not improved over the years. Even so, it has been found that growth in international trade between the two countries has the potential to positively benefit Peru's inclusive economic growth. With global development still on the rise, it is pivotal for us to ensure that all actors of society can benefit from that development, and not just the most privileged. Advocating for the importance of promoting openness in trade, International Trade and Inclusive Economic Growth highlights China and Peru's unique relationship to prioritize fair and equitable growth for all.
Keywords: Economic development -- Peru -- Case studies.; Income distribution -- Peru -- Case studies.; Marginality, Social -- Economic aspects -- Peru -- Case studies.; Equality -- Economic aspects -- Peru -- Case studies.; Peru -- Commerce -- China -- Case studies.; China -- Commerce -- Peru -- Case studies.; Business & Economics -- Development -- Economic Development.; Development economics and emerging economies.; elektronické knihy; electronic books